The Analysis of Threats and Opportunities in Sustainable Irrigation Development in Lesotho - M., Moses M. (Information Management and Business Review, 2014)
This paper analyzes threats and opportunities in sustainable irrigation development in Lesotho. The addressed research question is what threats and opportunities are there in irrigation projects backed by the government of Lesotho (GoL) for sustainable development and income generation in the rural areas for subsistence farmers. Threats to irrigation projects pose a problematic situation with a high possibility for project failure in attaining sustainable development. They need to be analytically identified for the provision of solutions at the project planning, implementation, monitoring and evaluation processes. The study has adopted the in-depth interviews for problems and opportunities identification with the participation of 63 irrigating farmers as respondents. Revealing threats against opportunities enable proper irrigation projects planning and implementation and therefore successful and sustainable irrigation development in Lesotho. Indepth field interviews’findings are on farmers in eight project sites selected by the Ministry of Agriculture (MoA) for further irrigation development with the backing of Food and Agricultural Organization (FAO). The eight sites are (1) Semonkong Ha Lesala and (2) Semonkong Ha Sechache, in Maseru district, (3) Ha Rasekila in Butha-Buthe district, (4) Qopo Ha Molefi in Berea district, (5) Maphutseng in Mohale’s Hoek district, (8) Qhoalinyane Ha Semethe and (7) Qhoalinyane, in Qacha’s Nek district, and lastly (8) Ha Makoae in Quthing district. The main implementing agency for this Water Control Component of the Special Programme for Food Security is the MoA in Lesotho.